2016
DOI: 10.1056/nejmoa1603800
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Herpes Zoster Subunit Vaccine in Adults 70 Years of Age or Older

Abstract: BACKGROUNDA trial involving adults 50 years of age or older showed that the herpes zoster subunit vaccine (HZ/su) containing recombinant varicella-zoster virus glycoprotein E and the AS01 B adjuvant system was associated with a risk of herpes zoster that was 97.2% lower than that associated with placebo. A second trial was performed concurrently at the same sites and examined the safety and efficacy of HZ/su in adults 70 years of age or older . METHODSThis randomized, placebo-controlled, phase 3 trial was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
639
2
17

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 789 publications
(729 citation statements)
references
References 31 publications
23
639
2
17
Order By: Relevance
“…HZ/su consists of 50 µg of recombinant VZV antigen (glycoprotein E) which directs the immune response to the virus itself, combined with the AS01B adjuvant system to stimulate T cell immunity to recombinant proteins [106]. As described in detail elsewhere [106], two very large multicenter-blinded RCTs reported that, among participants who had received two doses of Hz/su, VE against zoster was 97.2% (95% CI 93.7–99.0%) for adults aged ≥50 years [107] and 89.8% (95% CI 84.2–93.7%) for those aged ≥70 years [108]. In a pre-specified analysis of data pooled from both trials, the VE against PHN was 88.8% (95% CI 68.7–97.1%).…”
Section: Newer Developments In Zoster Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations
“…HZ/su consists of 50 µg of recombinant VZV antigen (glycoprotein E) which directs the immune response to the virus itself, combined with the AS01B adjuvant system to stimulate T cell immunity to recombinant proteins [106]. As described in detail elsewhere [106], two very large multicenter-blinded RCTs reported that, among participants who had received two doses of Hz/su, VE against zoster was 97.2% (95% CI 93.7–99.0%) for adults aged ≥50 years [107] and 89.8% (95% CI 84.2–93.7%) for those aged ≥70 years [108]. In a pre-specified analysis of data pooled from both trials, the VE against PHN was 88.8% (95% CI 68.7–97.1%).…”
Section: Newer Developments In Zoster Vaccinesmentioning
confidence: 99%
“…First, the VE of HZ/su against zoster is substantially higher overall (91% [108] versus 51.3% [79]). Second, theoretically HZ/su has greater potential for use in immunosuppressed patients, as it is not a live vaccine so does not pose risks of triggering varicella- or zoster-like illnesses; it has shown promise in phase I/II trials in severely immunocompromised patients [106].…”
Section: Newer Developments In Zoster Vaccinesmentioning
confidence: 99%
See 1 more Smart Citation
“…These adverse reactions tended to be transient, mild to moderate reactions, with a median duration of 2-3 days for injection site reactions and 1-2 days for systemic reactions. Systemic reactions were more frequently reported in HZ/su vaccine recipients (53.0%) 5 than in recipients of live attenuated vaccine (25%) 8 . Importantly, rates of serious adverse events, immune-mediated disease and deaths did not differ between HZ/su vaccine and placebo groups.…”
mentioning
confidence: 99%
“…In the study, known as ZOE-70, 13,900 participants with a mean age of 75.6 years were recruited from 18 countries and randomly allocated to receive either two doses of an investigational herpes zoster subunit vaccine (HZ/su; GSK vaccines) or placebo 5 . The new vaccine contained 50 µg of recombinant VZV glycoprotein E and the liposome-based AS01b adjuvant system, which enhances CD4+ T-cell and humoral immune responses to recombinant proteins.…”
mentioning
confidence: 99%